Information security of business networks - A. S. Losev (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim of the work is to improve the information security of businesstype networks, as the most susceptible to external threats for the purpose of commercial espionage.Method. The study is based on the use of an original mathematical algorithm that allows clustering networks of arbitrary topology and constructing a partial order matrix. On the one hand, clustering allows you to identify network agents that have the same information access to the network, on the other hand, partial order reflects the position of a single cluster in the hierarchical structure of the entire network.Result. This approach allows assessing the potential threat to the network depending on the position of the agent in the network that has been attacked. On its basis, a methodology has been developed to determine the degree of openness of an entrepreneurial network to the influence of external factors for each agent of the network. It allows you to identify network agents that require increased security in relation to external influences, since a potential attack on them has the most negative consequences for the entire connection, which emphasizes the practical significance of the result.Conclusion. The developed technique is practically significant and can be used to assess the information security or integrity of a network of any nature, represented as a directed graph.